2016
DOI: 10.1016/j.physbeh.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of posttraumatic stress disorder versus resilience on nocturnal autonomic nervous system activity as functions of sleep stage and time of sleep

Abstract: Posttraumatic stress disorder (PTSD) has been associated with sleep disturbances including alterations in sleep stages and recently, elevated nocturnal autonomic nervous system (ANS) arousal (i.e., dominance of the sympathetic nervous system over the parasympathetic nervous system). Data suggest that sleep contributes to the regulation of ANS activity. In our previous ambulatory heart rate variability (HRV) monitoring study, strong relationships between sleep and nocturnal ANS activity in resilient participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
2
14
3
Order By: Relevance
“…This finding is generally consistent with prior studies suggesting reduced parasympathetic function during sleep in those with PTSD [19,20]. As discussed above, Kobayashi and colleagues [17] conducted the only other study examining HF-HRV by sleep type in those with PTSD. In contrast with our study, Kobayashi and colleagues found a group-by-sleep-type interaction with the PTSD group having greater REM-NREM differences in HF-HRV than resilient individuals.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This finding is generally consistent with prior studies suggesting reduced parasympathetic function during sleep in those with PTSD [19,20]. As discussed above, Kobayashi and colleagues [17] conducted the only other study examining HF-HRV by sleep type in those with PTSD. In contrast with our study, Kobayashi and colleagues found a group-by-sleep-type interaction with the PTSD group having greater REM-NREM differences in HF-HRV than resilient individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Only one study has examined trends in HF-HRV across sleep in those with PTSD. Kobayashi and colleagues (discussed above) [17] found a significant decline in HF-HRV across successive NREM cycles across the night, but the rate of decline did not differ between groups. No changes were found in HF-HRV activity across successive REM sleep cycles.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Subjects exposed to extreme conditions and environments display astounding adaptive potential, which ultimately ensures optimal adjustment to current organismic demands and external stress (Kälin et al, 2012 ; Gunga, 2014 ). Assessment of autonomic cardiac modulation by means of heart rate variability (HRV) has shown to be a reliable tool to evaluate not only physiological changes (Taralov et al, 2015 ; Kobayashi et al, 2016 ), but also psychological aspects of human reactive adaptation to different stressors (Souza et al, 2013 ). Therefore, HRV assessment may describe human resilience, as it represents a bridge between physiology and psychology, and, by integrating these two aspects, it mirrors human adaptive ability (Thayer et al, 2009 ; Spangler and Friedman, 2015 ).…”
Section: Introductionmentioning
confidence: 99%